2016
DOI: 10.3906/sag-1507-31
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic isotretinoin treatment on skin biophysicalparameters among patients with acne vulgaris*

Abstract: Treatment with systemic isotretinoin reduces sebum secretion and stratum corneum hydration and increases skin temperature, suggesting that isotretinoin may partially improve the biophysical characteristics of the skin among patients with acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…It is very important to know the impact of cosmetological procedures and treatment on the parameters of the skin in order to choose the periprocedural care. [11][12][13] The results of our research showed a decrease in the secretion of sebum on the face, which is confirmed by the studies of Barakat et al, which showed a 31% reduction in the surface of the sebaceous glands after the IPL treatment. No neutrophils were observed in the biopsy specimen, and total inflammation was reduced by 36%.…”
Section: Re Sultssupporting
confidence: 90%
“…It is very important to know the impact of cosmetological procedures and treatment on the parameters of the skin in order to choose the periprocedural care. [11][12][13] The results of our research showed a decrease in the secretion of sebum on the face, which is confirmed by the studies of Barakat et al, which showed a 31% reduction in the surface of the sebaceous glands after the IPL treatment. No neutrophils were observed in the biopsy specimen, and total inflammation was reduced by 36%.…”
Section: Re Sultssupporting
confidence: 90%
“…The main aim of the drugs used to treat acne, including isotretinoin, is to reduce sebum secretion [ 87 ]. This is supported by a study by Colgecen et al [ 86 ], in which it was observed that treatment with systemic isotretinoin resulted in a reduction in sebum secretion, and thus improved the biophysical properties of the skin of patients with acne vulgaris. The results of measurements of skin biophysical indices before and after isotretinoin treatment by Kmieć et al [ 26 ] also showed a reduction in the severity of sebum secretion after the intervention.…”
Section: Discussionsupporting
confidence: 55%
“…A reduction in mean TEWL values after 6 weeks of isotretinoin treatment for acne and rosacea was also observed by Kim et al [ 85 ]. On the other hand, Kmieć et al [ 26 ] observed an increase in TEWL values in acne patients receiving isotretinoin therapy, and Colgecen et al, observed no difference in TEWL values after 3 months of isotretinoin treatment [ 86 ]. Orally administered evening primrose oil improved TEWL in healthy adults [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin parameters, such as sebum production, melanin content, moisturization, TEWL, and erythema, were assessed using MPA‐5 diagnostic apparatus equipped with a sensor of external conditions consisting of Tewameter TM300, Mexameter MX 18, Corneometer CM825, and Sebumeter SM815 3 . Çölgeçen et al found a significant decrease in sebum level and stratum corneum hydration in 19 patients using 0.5–0.75 mg/kg/day isotretinoin for 3 months but found no difference in TEWL values 22 . Kmiec et al measured sebum, hydration, TEWL, erythema, and pH values before and after treatment to detect the mucocutaneous adverse effects of isotretinoin and found a significant reduction in all parameters compared to before.…”
Section: Discussionmentioning
confidence: 99%